Ocular toxoplasmosis II: clinical features, pathology and management. (17th September 2012) - Butler, Nicholas J; Furtado, João M; Winthrop, Kevin L; Smith, Justine R
Abstract The term, ocular toxoplasmosis, refers to eye disease related to infection with the parasite, Toxoplasma gondii. Recurrent posterior uveitis is the typical form of this disease, characterized by unilateral, necrotizing retinitis with secondary choroiditis, occurring adjacent to a pigmented retinochoroidal scar and associated with retinal vasculitis and vitritis. Multiple atypical presentations are also described, and severe inflammation is observed in immunocompromised patients. Histopathological correlations demonstrate focal coagulative retinal necrosis, and early in the course of the disease, this inflammation is based in the inner retina. For typical ocular toxoplasmosis, a diagnosis is easily made on clinical examination. In atypical cases, ocular fluid testing to detect parasite DNA by polymerase chain reaction or to determine intraocular production of specific antibody may be extremely helpful for establishing aetiology. Given the high seroprevalence of toxoplasmosis in most communities, serological testing for T. gondii antibodies is generally not useful. Despite a lack of published evidence for effectiveness of current therapies, most ophthalmologists elect to treat patients with ocular toxoplasmosis that reduces or threatens to impact vision. Classic therapy consists of oral pyrimethamine and sulfadiazine, plus systemic corticosteroid. Substantial toxicity of this drug combination has spurred interest in alternative antimicrobials, as well as local forms of drug delivery. At this time, however, no therapeutic approach is curative of ocular toxoplasmosis.